The Halogen Effect on the Magnetic Behaviour of Dimethylformamide Solvates in [Fe(halide-salEen)2]BPh4 - Marques, Rafaela T. (2022)
Funding Research was funded by Fundação para a Ciência e a Tecnologia (FCT): projects UIDB/00100/2020, UIDP/00100/2020, LA/P/0056/2020, UIDB/04046/2020, UIDP/04046/2020, UIDB/50006/2020, UIDP/50006/2020 and LA/P/0008/2020, UIDB/04378/2020, UIDP/04378/2020, and LA/P/0140/2020, PTDC/QUI-QFI/29236/2017, PTDCQUI-QIN0252_2021, CEECIND/00509/2017; Fonds de la Recherche Scientifique (FNRS): PDR T.0095.21); Portugal2020: CENTRO-01-0145-FEDER-000018; Royal Society of Chemistry (RSC): R21-7511142525. Acknowledgments Centro de Química Estrutural (CQE) and Institute of Molecular Sciences (IMS) acknowledge the financial support of Fundação para a Ciência e a Tecnologia (FCT): Projects UIDB/00100/2020, UIDP/00100/2020, and LA/P/0056/2020, respectively. BioISI acknowledges FCT for financial support (UIDB/04046/2020, UIDP/04046/2020). This work was supported by the FNRS (PDR T.0095.21). Clara S. B. Gomes acknowledges the Associate Laboratory for Green Chemistry—LAQV, the Applied Molecular Biosciences Unit—UCIBIO and Associated Laboratory i4HB, which are financed by national funds from FCT (UIDB/50006/2020, UIDP/50006/2020 and LA/P/0008/2020, UIDB/04378/2020 and UIDP/04378/2020, and LA/P/0140/2020, respectively). Sónia Barroso thanks project SmartBioR for financial support (CENTRO-01-0145-FEDER-000018)and Centro de Química Estrutural for the access to crystallography facilities. Nuno A. G. Bandeira gratefully acknowledges the NanoBioSolutions FCT grant PTDC/QUI-QFI/29236/2017 for the computational infrastructure. Paulo N. Martinho thanks FCT and RSC for financial support (grants PTDCQUI-QIN0252_2021 and R21-7511142525). Paulo N. Martinho also thanks FCT for the contract CEECIND/00509/2017.